2009
DOI: 10.3109/10550490903077762
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Impairment in Ecstasy/Polydrug and Cannabis-Only Users

Abstract: The present study investigated aspects of sleep quality in ecstasy and cannabis users. Twohundred and twenty seven participants (117 ecstasy/polydrug users, 53 cannabis users and 57 drug naive participants) took part. The participants completed measures of daytime sleepiness, and indicators of sleep quality. The results demonstrated that ecstasy/polydrug users viewed themselves as being more evening types and having poorer sleep quality than cannabis users and drug naive participants. They were also more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…However, although patients with SUD suffer from reduced HRQL (eg, 18), the relationship between sleep problems and HRQL in these patients is still not fully understood. Several studies dealt with sleep problems in homogeneous populations of patients dependent on alcohol, cannabis or other substances but none addressed the relationship between sleep disorders and HRQL in a naturalistic sample of polydrug‐using inpatients, who also suffer from co‐occurring psychiatric disorders (COD). The HRQL of COD patients is even more affected than among patients who only suffer from SUD .…”
Section: Introductionmentioning
confidence: 99%
“…However, although patients with SUD suffer from reduced HRQL (eg, 18), the relationship between sleep problems and HRQL in these patients is still not fully understood. Several studies dealt with sleep problems in homogeneous populations of patients dependent on alcohol, cannabis or other substances but none addressed the relationship between sleep disorders and HRQL in a naturalistic sample of polydrug‐using inpatients, who also suffer from co‐occurring psychiatric disorders (COD). The HRQL of COD patients is even more affected than among patients who only suffer from SUD .…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with the findings of Landolt and Gillin (31), Teplin et al (32), Fisk and Montgomery, and also findings of Peles et al In other words, people with high quality sleep have less substance-related disorders. In order to explain this, it could be argued that people with less useful sleep and delayed sleep generally experience less sleep (33,34). They may have active and passive readiness for inclination towards substance-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as sleep was not the major focus of many of the early studies, specific information about which components of sleep were disrupted or what aspects of ecstasy use were associated with changes in sleep were not investigated. More recent studies have examined sleep variables in greater detail and found that ecstasy users report poor sleep quality, [31][32][33] more restless sleep for 48 h post-ecstasy use 29 and an evening-type preference. 31,33,35 However, the use of validated sleep instruments to examine sleep parameters is relatively new in this field.…”
Section: Subjective Measures Of Sleepmentioning
confidence: 99%
“…More recent studies have examined sleep variables in greater detail and found that ecstasy users report poor sleep quality, [31][32][33] more restless sleep for 48 h post-ecstasy use 29 and an evening-type preference. 31,33,35 However, the use of validated sleep instruments to examine sleep parameters is relatively new in this field. 34,36 Use of such measures is beneficial given that they provide information that can be compared to other clinical populations suffering from sleep disturbances and used to identify clinically relevant levels of disturbance.…”
Section: Subjective Measures Of Sleepmentioning
confidence: 99%